Rationale, Design and Validity of Immersive Virtual Reality Exercises in Cognitive Rehabilitation - Janavičiūtė, Jovita; Paulauskas, Andrius; Šinkariova, Liuda; Blažauskas, Tomas; Kiudys, Eligijus; Janonis, Airidas; Girdžiūna, Martynas (Information and Software Technologies, 2022)
The application of virtual reality solutions for rehabilitation is hard, because stroke patients usually suffer motor, gait, and visual field impairments. This article discusses important aspects that should be addressed when developing programs of a similar nature. The system for stroke patients’ cognitive rehabilitation is introduced. The development process of the system is described in detail. The results were validated using the Content Validity Index (CVI). The validation results revealed that the tasks created are suitable for stroke patients’ cognitive rehabilitation.